Rationale and design of the peripheral nerve tumor registry: an observational cohort study. (2nd January 2023) - Dengler, Nora F.; Scholz, Christoph; Beck, Jürgen; Uerschels, Anne-Kathrin; Sure, Ullrich; Scheller, Christian; Strauss, Christian; Martin, Daniel; Schackert, Gabriele; Heinen, Christian; Woitzik, Johannes; McLean, Anna Lawson; et al.
ABSTRACT: Aim: Peripheral nerve tumors (PNT) are rare lesions. To date, no systematic multicenter studies on epidemiology, clinical symptoms, treatment strategies and outcomes, genetic and histopathologic features, as well as imaging characteristics of PNT were published. The main goal of our PNT Registry is the systematic multicenter investigation to improve our understanding of PNT and to assist future interventional studies in establishing hypotheses, determining potential endpoints, and assessing treatment efficacy. Methods: Aims of the PNT registry were set at the 2015 Meeting of the Section of Peripheral Nerve Surgery of the German Society of Neurosurgery. A study protocol was developed by specialists in PNT care. A minimal data set on clinical status, treatment types and outcomes is reported by each participating center at initial contact with the patient and after 1 year, 2 years, and 5 years. Since the study is coordinated by the Charité Berlin, the PNR Registry was approved by the Charité ethics committee (EA4/058/17) and registered with the German Trials Registry (www.drks.de ). On a national level, patient inclusion began in June 2016. The registry was rolled out across Europe at the 2019 meeting of the European Association of Neurosurgery in Dublin. Results: Patient recruitment has been initiated at 10 centers throughout Europe and 14 additional centers are currently applying for local ethics approval. Conclusion: To date, the PNT registry has grown into an international study group with regular scientific and clinical exchange awaiting the first results of the retrospective study arm.